Comparison of two systems for rigidly connecting 2.0-mm bone screws to an implantable device: in vitro stability testing - J.-P. van Loon,* L. G. M. de Bont,* G. J. Verkerke (Blackwell Synergy, 2000)
For a number of implantable devices, screw fixation to bony structures results in stable fixation. For conventional screw fixation, the diameter of the screw holes in the device is slightly larger than the outer diameter of the screws.